Cervical root schwannoma: a case series - Nikte, Harshad; Virmani, Nitish; Dabholkar, Jyoti (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Cervical root schwannoma is an infrequent benign peripheral nerve tumor though those arising from high cervical spinal root are common amongst the spinal schwannomas. This mass commonly presents as a slow growing, asymptomatic, solitary neck mass with rare potential of malignant degeneration. Displacement of Internal jugular vein and carotids anteriorly is frequently seen though abutment of esophagus is uncommon. Pre operative diagnosis can be established with imaging and Fine needle aspiration cytology (FNAC). Complete Surgical excision is the treatment of choice. Horner’s syndrome is the most common post operative neurological manifestation. Here we have recorded clinical features intra-operative findings and surgical histopathology. We have described a case of 19 year old male with cellular schwannoma of cervical sympathetic chain with intraspinal extension and arising from C5-C8 level. Another case of cervical root schwannoma is described in a 5 year old girl arising at C4-C5 level. Complete surgical excision was done for both patients with no postoperative neurological affection. The clinico-pathological evaluation and management are described